Context and Validation of the Subjective Underemployment Scale Among Turkish Employees. (May 2021) - Buyukgoze-Kavas, Aysenur; Allan, Blake A.; Turan, Merve; Kirazci, Furkan
The purpose of the current study was to validate the Turkish version of the Subjective Underemployment Scales (SUS; Allan et al., 2017), a recently developed measure aimed at assessing the six components of underemployment: pay, status, field, hours, involuntary temporary work, and poverty wage employment. The proposed six-factor structure of the SUS was empirically supported among a diverse group of Turkish employees (211 female, 190 male with a mean age of 32.31; ranging from 20 to 63). Consistent with the original study, a six-factor correlational model produced better fit indices than single factor, higher order, and bifactor model. A series of multigroup confirmatory factor analyses provided evidence for configural, metric, and scalar invariance of the SUS, suggesting that the structure of the Turkish version of the scale was equivalent across gender, income, and social class groups. The results of the correlational analyses supported validity by significant positive correlations with measures of overqualification and withdrawal intentions and significant negative correlations with measures of job satisfaction, pay satisfaction, and meaningful work. The results of the study indicated the Turkish version of the SUS (T-SUS) provided a valid and reliable assessment of underemployment among Turkish employees. Also, findings of the present study help to gain an understanding of subjective underemployment experiences of Turkish employees and provide a framework for practitioners; employers, researchers, and policymakers to determine potential need for improvement through components of underemployment.